The Emergence, Development, and Morphology of Gedaref City (Journal of Libya for geographical studies, 2025)
This paper examines the city of Gedaref in terms of its origin, stages of growth and development, and the events that influenced this progression. It also analyzes the general appearance of the city by studying the elements that shaped its current form, including a morphological analysis of the city plan, building patterns, and land use. The study aims to identify the reasons behind the city's establishment in its current location, trace its stages of expansion, and analyze its urban morphology.To achieve these objectives, the study utilized field tools to collect data through observation, interviews, questionnaires, maps, and satellite imagery. Statistical methods and computer software were used for data analysis. The historical approach was adopted to track the city's growth stages, along with descriptive analysis of field data and official sources.The study concluded that the city was established at its current location for military purposes during the Turkish era. It also revealed that mechanized agriculture in the region played a major role in the city's growth and development. The study recommended addressing the planning imbalances of previous schemes and adopting more flexible planning approaches that ensure equitable service distribution. Additionally, it emphasized the need to continue decongesting the city center and developing a ring road network to facilitate access to various land uses.
Keywords: Urban morphology; mechanized agriculture; land use; city plan; migration